Effects of antipsychotics on heart rate in treatment of schizophrenia: a systematic review and meta-analysis. (June 2022) - Huhn, Maximilian; Arndt, Thomas; Schneider-Thoma, Johannes; Leucht, Stefan
Background: Antipsychotics are the treatment of choice in the therapy of schizophrenia. These drugs can be associated with changes in heart rate, but this question has never been examined systematically. Objective: We aimed to analyse changes in heart rate during treatment with antipsychotics using the frequency of tachycardia and bradycardia events. Design: For this systematic review and meta-analysis, we included all randomized controlled trials for the acute treatment of schizophrenia comparing antipsychotics head-to-head or with placebo. Data Sources and Methods: We searched Embase, MEDLINE, PsycINFO, PubMed, BIOSIS, Cochrane Central Register of Controlled Trials (CENTRAL), WHO International Clinical Trials Registry Platform and ClinicalTrials.gov (last search June 2021). Two authors independently selected studies and extracted data. We conducted pairwise meta-analyses using a random-effects model. Outcomes were tachycardia and bradycardia events. Results: We found 469 trials meeting the inclusion criteria. Seventy-seven studies with 16, 907 participants provided data on tachycardia or bradycardia events. We found no significant differences between antipsychotics and placebo or between antipsychotics for bradycardia events based on sparse data. Antipsychotics had a higher risk for tachycardia events compared with placebo [ N  = 37, n  = 7827, risk ratio (RR) = 1.83, 95% confidence interval (CI) = 1.40–2.41], with large differences between the individual substances (iloperidone RR = 14.05, chlorpromazine RR = 4.84, loxapine RR = 4.52, risperidone RR = 3.38, quetiapine RR = 2.64, paliperidone RR = 1.65). Some head-to-head comparisons were also significantly different: olanzapine versus haloperidol RR = 2.87, chlorpromazine versus thiothixene RR = 2.92, quetiapine versus lurasidone RR = 3.22, risperidone versus aripiprazole RR = 4.37, iloperidone versus ziprasidone RR = 4.65). Conclusion: Many studies do not report data for cardiac outcomes, but the available evidence indicates that treatment with antipsychotics raises the risk for tachycardia. Therefore, especially patients with cardiac risk factors should be monitored closely during antipsychotic treatment. Registration: PROSPERO: CRD42014014919